2022
DOI: 10.2147/cia.s365282
|View full text |Cite
|
Sign up to set email alerts
|

The P.R.OS.T.A.T.E Nomogram for the Preoperative Prediction of Clinical Efficacy of Transurethral Resection of the Prostate in Benign Prostatic Hyperplasia Patients

Abstract: Transurethral resection of the prostate (TURP) is often indicated for benign prostatic hyperplasia (BPH). Some patients, however, fail to adequately respond to these interventions. Accordingly, a powerful prediction model for TURP efficacy is warranted. This study aimed to create a nomogram with preoperative parameters for the prediction of individual TURP efficacy. Methods: Clinical data from 356 BPH subjects who underwent TURP were retrospectively collected between November 2015 and June 2021 for nomogram de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Tian et al [24]combined age, IPSS, IPP, bladder wall thickness, peripheral prostatic belt thickness, and migratory zone thickness to construct a prediction model for predicting post-TURP outcomes in patients with BPH, which had an AUC = 0.806 (95% CI 0.733-0.879); however, it is worth noting that the researchers did not analyze the model with clinical decision curves and that most of the predictive factors were obtained by ultrasonography. factors were overwhelmingly obtained from ultrasound, resulting in a greater degree of possible measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al [24]combined age, IPSS, IPP, bladder wall thickness, peripheral prostatic belt thickness, and migratory zone thickness to construct a prediction model for predicting post-TURP outcomes in patients with BPH, which had an AUC = 0.806 (95% CI 0.733-0.879); however, it is worth noting that the researchers did not analyze the model with clinical decision curves and that most of the predictive factors were obtained by ultrasonography. factors were overwhelmingly obtained from ultrasound, resulting in a greater degree of possible measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Li et al [ 22 ] found that patient age, BMI, duration of history of LUTS, and prostate volume were independent influences for postoperative urge incontinence through logistic regression models. Ye Tian et al [ 23 ] reported that the P.R.OS.T.A.T.E. regression model could predict the outcome of BPH surgery in 2022.…”
Section: Discussionmentioning
confidence: 99%
“…49 Tian et al have developed a nomogram to predict the efficacy of TURP, but this mainly addresses the success of improving the flow rate and does not address the development or persistence of storage OAB/LUTS. 50 As can be seen from the above, storage and/or voiding LUTS can either persist or develop after TURP surgery and urodynamics is key to the assessment of these patients with bothersome LUTS following surgery. However, further research with large clinical trials is needed where urodynamics is utilized before TURP and then repeated post-TURP to be able to understand the pathophysiology of LUTS postsurgery, allowing better counseling of patients before surgery.…”
Section: What Is the Role Of Uncorrected Obstruction Or Detrusor Unde...mentioning
confidence: 99%
“…Tian et al have developed a nomogram to predict the efficacy of TURP, but this mainly addresses the success of improving the flow rate and does not address the development or persistence of storage OAB/LUTS 50 …”
Section: What Is the Role Of Uncorrected Obstruction Or Detrusor Unde...mentioning
confidence: 99%